PERKEMBANGAN PERBANKAN SYARIAH DI ERA DIGITALISASI - bagas oges bryan pratama; Muhammad Iqbal Fasa; Is Susanto (PT. Intelek Cendikiawan Nusantara, 2024)
The rapid advancement of technology today is having a significant impact on various aspects of life, including finance. For years, financial transactions were primarily conducted through conventional banking services that relied on face-to-face interactions and manual processes. However, the emergence of Financial Technology, or FinTech, has brought about major changes how people interact with financial services. FinTech offers more efficient, faster, and easily accessible solutions, such as digital payments, online loans, and app-based investments. With the rise of various FinTech platforms, the role of traditional banks is beginning to be threatened. People are now opting for more practical and innovative methods to manage their finances. This poses challenges for banks that continue to use conventional methods. They must adapt and innovate to remain relevant in an increasingly digital financial ecosystem. Banks that do not respond to these changes risk losing customers, particularly younger generations who are more comfortable with technology. To address this situation, banks need to integrate technology into their services, such as providing user-friendly mobile banking applications and leveraging big data to better understand customer needs. Additionally, collaboration with FinTech companies can be a strategic move to enhance services and attract more customers. By taking these steps, traditional banks can maintain their position and continue to serve as pillars in the evolving financial system. The rapid development of technology is now facilitating human activities across various fields. Until now, financial transactions have typically been completed through conventional banking services. However, with ongoing advancements, a new platform Financial Technology